Transient Reflexive Pain Responses and Chronic Affective Nonreflexive Pain Responses Associated with Neuroinflammation Processes in Both Spinal and Supraspinal Structures in Spinal Cord-Injured Female Mice - Castany, Sílvia; Bagó-Mas, Anna; Vela, José Miguel; Verdú, Enrique; Bretová, Karolina; Svobodová, Viktorie; Dubový, Petr; Boadas-Vaello, Pere (International journal of molecular sciences, 2023)
Central neuropathic pain is not only characterized by reflexive pain responses, but also emotional or affective nonreflexive pain responses, especially in women. Some pieces of evidence suggest that the activation of the neuroimmune system may be contributing to the manifestation of mood disorders in patients with chronic pain conditions, but the mechanisms that contribute to the development and chronicity of CNP and its associated disorders remain poorly understood. This study aimed to determine whether neuroinflammatory factor over-expression in the spinal cord and supraspinal structures may be associated with reflexive and nonreflexive pain response development from acute SCI phase to 12 weeks post-injury in female mice. The results show that transient reflexive responses were observed during the SCI acute phase associated with transient cytokine overexpression in the spinal cord. In contrast, increased nonreflexive pain responses were observed in the chronic phase associated with cytokine overexpression in supraspinal structures, especially in mPFC. In addition, results revealed that besides cytokines, the mPFC showed an increased glial activation as well as CX3CL1/CX3CR1 upregulation in the neurons, suggesting the contribution of neuron-glia crosstalk in the development of nonreflexive pain responses in the chronic spinal cord injury phase.
Keywords: cytokines; poranění míchy; neuralgie; Neuroglia; neuroglie; Mice; spinal cord injury; Neuroinflammatory Diseases; Animals; ženské pohlaví; chemokines; zvířata; neuroinflammation; central neuropathic pain; Neuralgia; chronic pain; Spinal Cord; myši; gliosis; Female; Spinal Cord Injuries; mícha; neurozánětlivé nemoci; CX3CL1/CX3CR1